Analisis Terhadap Kemampuan Berpikir Kritis Peserta Didik melalui Pembelajaran Papan Permainan Evaluasi Trigonometri - Usep Kosasih; Isna Fitriana; Samnur Saputra; Abdul Wahid (Universitas Samudra, 2022)
This research was motivated by the assumption that students stated that mathematics was a scary subject and boredom so that students' negative perceptions of learning mathematics emerged. One way to overcome this is to innovate learning. The learning innovation carried out in this research is by using game media. This study aims to determine how the learning outcomes of students who learn through trigonometry evaluation board games are viewed from critical thinking skills, to determine student responses to learning evaluations through trigonometry evaluation board games and to find out how practical the implementation of trigonometric evaluation board games in trigonometry learning is. This research is a descriptive qualitative research. The subjects of this study were students of class X MIPA, one of the schools in the city of Bandung, for the academic year 2021/2022 as many as 34 students were taken using purposive sampling technique. The data collection technique used a final test which consisted of three questions, a questionnaire, validation and observation. The results showed that the learning outcomes of students who learned through the trigonometric evaluation board game in terms of critical thinking skills belonged to the very well, the student's response to the evaluation of learning through the trigonometric evaluation board game was classified in the very positive category and the evaluation of learning through the trigonometric evaluation board game going very well.